Vaksinasi covid-19 dan kinerja keuangan perusahaan properti dan real estate di Bursa Efek Indonesia - Riana Susanti; Askardiya Radmoyo Adji (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The implementation of the Covid-19 national vaccination is one of the game changers that is expected to help economic recovery in the future. This study aims to analyze the impact of the Covid-19 vaccination implementation on the financial performance of property and real estate sector companies listed on the Indonesia Stock Exchange. The research sample is 72 property and real estate sector companies listed in the third quarter of 2020 and the third quarter of 2021. Data analysis uses the Wilcoxon Signed Rank Test. The test results show an increase in the liquidity ratio and profitability ratio but a decrease in the leverage ratio and activity ratio. However, there was no significant difference in testing all ratios between before and after the Covid-19 vaccination was carried out. This study fills the gap from previous research, namely providing an analysis of the impact of Covid-19 vaccination on the financial performance of companies on the Indonesia Stock Exchange, especially in the property sector. Further research may include several other variables that may affect the company's performance and which have not been considered in this study.